2015
DOI: 10.1161/circulationaha.114.013520
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Biodegradable-Polymer Biolimus-Eluting Stents

Abstract: rug-eluting stents (DES) with biodegradable polymers were developed to be as effective as second-generation durable-polymer drug-eluting stents and as safe after 1 year as bare-metal stents (BMS).1 Thus, very late stent thrombosis (VLST: beyond 1 year after implantation), which has been associated with the durable polymer of first-generation DES, Background-Biodegradable-polymer drug-eluting stents (BP-DES) were developed to be as effective as second-generation durable-polymer drug-eluting stents (DP-DES) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…Second, the mean age of our patients was lower than the mean ages of patients in the other studies. The mean age was 58 years in our study, as opposed to 65 years in the studies by Lee and co-authors 11 and Tada and associates, 22 and 62 and 63 years in the studies by Smits and colleagues 21 and Kaiser and associates, 16 respectively.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Second, the mean age of our patients was lower than the mean ages of patients in the other studies. The mean age was 58 years in our study, as opposed to 65 years in the studies by Lee and co-authors 11 and Tada and associates, 22 and 62 and 63 years in the studies by Smits and colleagues 21 and Kaiser and associates, 16 respectively.…”
Section: Discussioncontrasting
confidence: 74%
“…[13][14][15][16][17] Trials have revealed the lower rates of MACE in short-and long-term follow-up after the DP-EES implantation in comparison to the earlier generation and have introduced the DP-EES as the standard of DES, versus other design improvements. 18 Investigators have also confirmed the superiority of the BP-BES over the first-generation DES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For only 6 of these trials, follow-up data between 2 and 5 years were available. 36,41,43,48,50,52 At longerterm follow-up, a significantly lower risk of stent thrombosis was observed with BP-DES compared with PP-DES (odds ratio, 0.43; 95% CI, 0.25-0.73; Figure 2A-2D). Although promising, this finding should be interpreted with caution.…”
Section: Bp-based Dessmentioning
confidence: 98%
“…3 In that trial, prasugrel was prescribed at the same doses as in the Garratt et al study and stopped after 12 months in all patients (A small number of patients with stable coronary artery disease and bare-metal stents were treated for 1 month only). The main difference between the 2 trials was the type of stent used: In BASKET-PROVE II, it was either a biodegradable-polymer or a durable-polymer "-limus" drug-eluting stent, whereas in the Garratt et al study, it was a paclitaxel-eluting stent.…”
Section: To the Editormentioning
confidence: 99%